2019
DOI: 10.3389/fimmu.2019.01424
|View full text |Cite
|
Sign up to set email alerts
|

A Modified mRNA Vaccine Targeting Immunodominant NS Epitopes Protects Against Dengue Virus Infection in HLA Class I Transgenic Mice

Abstract: Dengue virus (DENV) induces strong T and B cell responses upon infection. Hence, it is difficult to determine the contribution of cell-mediated immunity alone in the long lasting protection against DENV infection and disease. Numerous CD4+ and CD8+ T cell epitopes have been identified, mainly in the non-structural proteins of DENV. Taking into account the immunogenicity and peptide sequence conservation among the different DENV serotypes, a minimal DENV antigen, called DENV1-NS, has been designed. This antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 58 publications
0
56
0
Order By: Relevance
“…This is consistent with a previous report that mRNA vaccine with selected NS peptides provided partial protection in transgenic mice against experimental DENV infection. 54 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous report that mRNA vaccine with selected NS peptides provided partial protection in transgenic mice against experimental DENV infection. 54 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, for human T cells, prior exposure to DENV skewed the immunodominance of ZIKV-specific T cells toward non-structural proteins (35), yet these cross-activated T cells retained their ex vivo functionality (37). This cross-reactivity may be beneficial for clearing a secondary infection since it has been shown that a vaccine utilizing non-structural epitopes of DENV can protect against DENV infection in mice (38). Still, the broad question of whether flavivirus cross-reactive CD8 T cells are protective or pathological in nature remains to be resolved.…”
Section: Flavivirus Cross-reactive T Cell Responsesmentioning
confidence: 99%
“…One of the most widely studied of these vaccine platforms uses antigen-encoding nucleoside-modified mRNA encapsulated into lipid nanoparticles (mRNA-LNP) ( Pardi et al., 2015 ). Nucleoside-modified mRNA-LNP vaccines have induced protective immune responses against various pathogens in preclinical studies ( Awasthi et al., 2019 ; Espeseth et al., 2020 ; Freyn et al., 2020 ; Meyer et al., 2018 ; Pardi et al., 2017 , 2018a , 2018c ; Richner et al., 2017 ; Roth et al., 2019 ), in many cases, after administration of a single dose ( Freyn et al., 2020 ; Pardi et al., 2017 , 2018a , 2018c ). This vaccine type has been shown to elicit particularly strong CD4 + T cell, germinal center B cell and long-lived plasma cell responses associated with durable, protective neutralizing antibody responses ( Lindgren et al., 2017 ; Pardi et al., 2018a ).…”
Section: Introductionmentioning
confidence: 99%